Consumer loneliness: A systematic review and research agenda - Huang, Shanshan; Li, Mingfei (Frontiers in Psychology, 2023)
Treading on the heels of the spread of the coronavirus, the “loneliness virus” has been capturing territories globally. Consumers are not immune to loneliness. Although academics and the general public have recognized the devastating effects of loneliness, the academic attention given to consumer loneliness (CL) is scattered and fragmentary. The purpose of this article is to systematically review the antecedents (predictors and alleviators) and consequences (consumer behaviors, emotions, preferences, attitudes, and cognition) of CL in various consumption contexts. This review also presents findings on CL as a mediator and a moderator in consumer studies. This work adds to the growing body of CL literature by synthesizing the existing findings and knowledge. More importantly, we present a future research agenda by linking CL to significant research lines and detailed implications for practitioners in the marketplace.